Bubble-induced oscillating flow in microbubble emission boiling under highly subcooled conditions. (10th May 2023) - Tang, Jiguo; Li, Xiao; Xu, Lingmiao; Sun, Licheng
Abstract: Abstract : Microbubble emission boiling (MEB), a phenomenon that occurs under highly subcooled boiling conditions, can achieve a high heat flux beyond critical heat flux. MEB has been observed to differ from nucleate boiling and is always accompanied by the emission of microbubbles from an oscillating bubble. The heat transfer mechanism of MEB differs from that of nucleate boiling and remains elusive. In this study, we measure the behaviour of a vapour bubble and its induced liquid flow simultaneously during subcooled boiling using the high-speed two-phase particle image velocimetry method. Different from nucleate boiling, we observe a rapid oscillating flow outside the bubble that constantly attaches on the heating surface in MEB. The spatially and temporally averaged velocity magnitude values under this oscillating flow, and their dependency on liquid subcooling and heat flux, are quantified. Then we derive a scaling law for the heat transfer of MEB as a function of Péclet and Jacob numbers. With such correlations, we suggest that the oscillating flow induced by bubble oscillations is important to MEB, thus elucidating a different heat transport process from nucleate boiling.